Chordoid sarcoma arising with the triceps muscle : a case report - So, Marie Michelle Y.
A case of chordoid sarcoma which occured within the triceps muscle of a 59-year old male is reported. The light microscopic and histochemical features are presented with a review of the literature on chordoid sarcoma, particularly the ultrastructural findings.
Acta Medica Philippina, 1991 27 ( 1 ) pages 54-57
Keywords: Sarcoma